2002
DOI: 10.1037/h0095015
|View full text |Cite
|
Sign up to set email alerts
|

Culture, control, and family involvement: A comparison of psychosocial rehabilitation in India and the United States.

Abstract: Research has shown better prognosis rates for people with psychiatric disabilities in developing countries than in Western countries. By comparing psychosocial rehabilitation in India and the United States, this paper explores how cultual beliefs and practices impact the recovery of people with psychiatric disabilities. In India, an emphasis on interdependence, externalized locus of control, and family involvement, are significantfactors in caring for people with psychiatric disabilities. In contrast, rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…These different views may have been shaped by the home culture of the health professionals. Stanhope (2002) describes different allocation of responsibility over symptoms based on cultural backgrounds, with Western cultures more attuned to taking more personal responsibility. Health professionals need to be aware of the possible influence of religion on patients' acceptance and motivation during recovery and rehabilitation post-stroke, and how their own religious beliefs may influence their preparedness to work in culturally sensitive ways with patients.…”
Section: Resultsmentioning
confidence: 99%
“…These different views may have been shaped by the home culture of the health professionals. Stanhope (2002) describes different allocation of responsibility over symptoms based on cultural backgrounds, with Western cultures more attuned to taking more personal responsibility. Health professionals need to be aware of the possible influence of religion on patients' acceptance and motivation during recovery and rehabilitation post-stroke, and how their own religious beliefs may influence their preparedness to work in culturally sensitive ways with patients.…”
Section: Resultsmentioning
confidence: 99%
“…In illustration, Saltapidas and Ponsford (2008) found that patients with traumatic brain injury (TBI) from minority group 3 backgrounds in Australia scored lower in internal locus of control (LOC) than patients from the dominant English-speaking culture. This may reflect Western values that emphasise autonomy and self-responsibility, whilst in some non-Western cultures, LOC is more externalized, and the ill person is more likely to be viewed as dependent on the family and not responsible for self-managing the condition (Stanhope, 2002;Dalvandi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of family co-residence, however, varies in different familial and cultural contexts (Stanhope 2002). When a relative is ill, family care is generally seen as a priority in many ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…As normalization oftentimes drives social services and interventions, psychiatric rehabilitation commonly aims to enhance independence and individual productivity (Stanhope 2002), sometimes without specific guidelines. Research on practices to assist independence, however, is scarce.…”
Section: Introductionmentioning
confidence: 99%